Banking social responsibility and its influence on competitiveness - Bracamonte Carpio, Nataly Amelia (2021)
At the global level, the relevance of social responsibility is increasing; thus, it is essential to study the context of banking institutions; and determine how the social responsibility of these institutions influences the competitiveness of a Bank based in Tacna, year 2019. A basic, observational, explanatory transectional investigation was carried out. The sample consisted of Bank users, with a total sample of 384 clients. The instrument used was the questionnaire. Banking social responsibility has been found to significantly influence the bank's competitiveness. The bank social responsibility variable has a 72% level of influence on the competitiveness variable. (R2 significant according to the Nagelkerke indicator).